Spatial coding in two dimensions - Rubichi, Sandro; Vu, Kim-Phuong L.; Nicoletti, Roberto; Proctor, Robert W. (Psychonomic bulletin & review, 2006)
There has been growing interest in exploring human performance for situations in which stimuli and/or responses vary along both horizontal and vertical dimensions. Earlier studies indicated that there is a prevalence of the horizontal dimension over the vertical dimension in the spatial codes that are used for response selection. We review evidence about spatial coding for 2-D stimulus-response sets and accounts that have been proposed for explaining how it takes place. Particular attention is devoted to the relative salience account, which provides the most comprehensive explanation of 2-D spatial coding. We also evaluate the influence of speed of spatial code formation, number of reference frames, and learning on subjects' performance in 2-D tasks.